2008
DOI: 10.1542/peds.2007-1652
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Profiles in Children With Functional Urinary Incontinence Before and After Incontinence Treatment

Abstract: Since the 1980s, urinary incontinence and bed-wetting started to be seen as functional problems, with behavioral problems secondary to the bed-wetting. Behavioral problems in bed-wetting is studied extensively, but much less has been studied regarding behavioral problems in functional incontinence. What This Study AddsAbnormal behavior scores in children with functional incontinence were studied prospectively, before and after treatment for incontinence, as part of a randomized controlled trial. ABSTRACTOBJECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Schast et al reported a higher mean score for the PLUTSS in children with ADHD or learning disabilities [15]. Bael et al found that the TCS and EXTS improved after therapy in children with dysfunctional voiding, but that the scores did not change for urge incontinence [16]. In contrast, our study showed that patients with both urge incontinency and voiding postponement had higher TCS, INTS, and EXTS than did controls.…”
Section: Discussioncontrasting
confidence: 76%
“…Schast et al reported a higher mean score for the PLUTSS in children with ADHD or learning disabilities [15]. Bael et al found that the TCS and EXTS improved after therapy in children with dysfunctional voiding, but that the scores did not change for urge incontinence [16]. In contrast, our study showed that patients with both urge incontinency and voiding postponement had higher TCS, INTS, and EXTS than did controls.…”
Section: Discussioncontrasting
confidence: 76%
“…In a study by Bael et al [10] in 2008, they found that, before treatment of non-neurogenic bladder sphincter dysfunction (NNBSD) in the European bladder dysfunction group, behavioral problems were present in 19% of the children at a rate of 2:1 compared to normative population. After treatment of incontinence, the rate dropped to 11%, which was the same as the normative group.…”
Section: Neuropsychiatric Diseases and Voiding Issuesmentioning
confidence: 99%
“…They also noted that fathers of children with OAB had resolution of nocturnal enuresis at a later age than controls. Mothers of children with OAB or DV also reported on their current symptoms using the Urogenital Distress Inventory and demonstrated that symptoms of OAB-but not DVpersisted into adulthood, further supporting the concept that DV is more influenced by behavioral components than OAB [48].…”
Section: Association Of Childhood Symptoms In Adultsmentioning
confidence: 65%